Dietary Fiber and the Risk of Pancreatic Cancer. Issue 1 (January 2019) - Koulouris, Andreas I.; Luben, Robert; Banim, Paul; Hart, Andrew R.
Abstract : Objectives: High dietary fiber may protect against pancreatic ductal adenocarcinoma (PDAC). We investigated associations between fiber intake and the risk of PDAC using for the first time 7-day food diaries. Methods: Participants in the European Prospective Investigation Into Cancer–Norfolk completed the 7-day food diaries at recruitment. The cohort was followed up for 17 years to identify those who developed PDAC. Participants were divided into quintiles of fiber intake, and hazard ratios (HR) were estimated with their 95% confidence intervals (CIs). Fiber was tested for effect modification of high red and processed meat intake and smoking and the risk of PDAC. Results: No significant associations for any quintiles of intake (HR Q5 vs Q1, 1.08; 95% CI, 0.56–2.08) were detected with no trend across quintiles. A high-fiber diet modified positive associations between red and processed meats with the development of PDAC (HR trends, 0.89 [95% CI, 0.47–1.69] and 1.02 [95% CI, 0.55–1.88], respectively) but not those with lower fiber intake. Fiber intake did not modify the risk of PDAC in past and current smokers. Conclusion: The findings do not suggest that fiber protects against PDAC, although it may decrease potential deleterious effects of meats.